Immediate hypersensitivity reaction following liposomal amphotericin-B (AmBisome) infusion. (October 2014) - Nath, Proggananda; Basher, Ariful; Harada, Michiyo; Sarkar, Santana; Selim, Shahjada; Maude, Richard J; Noiri, Eisei; Faiz, Abul
Liposomal amphotericin-B (AmBisome) is now becoming first choice for the treatment of visceral leishmaniasis (kala-azar) patients due to high efficacy and less toxicity. The reported incidence of hypersensitivity reactions to liposomal amphotericin-B (AmBisome), especially during therapy, is very rare. We report two patients with kala-azar: one developed breathing difficulties and hypotension followed by shock and the other had facial angioedema with chest tightness during treatment. Both patients were managed with immediate action of injection: adrenaline, diphenhydramine and hydrocortisone. In our experience, AmBisome can cause severe hypersensitivity reactions that warrant proper support and close supervision.